The Enterprise and the Management. An Austrian Approach (2019)
The Austrian stream of economic thought has theorized, taking into account Karl Menger’s social sciences method, about social and business human organizations based on the existence of disperse and scattered knowledge in all individuals that make part of such organizations. This obliges to define mechanisms of governability and management for both the society and the companies. This article concentrates on describing the nature and possibilities of management of business organizations according to the Austrian stream.